2022
DOI: 10.3389/fimmu.2022.883605
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Changes of Basophil Hyperreactivity to Sweat in Patients With Well-Controlled Atopic Dermatitis

Abstract: BackgroundSweat aggravates atopic dermatitis (AD). In patients with AD, type-I hypersensitivity to sweat may be shown by histamine release from patients’ basophils in response to the semi-purified sweat antigen (QR), and the presence of specific immunoglobulin E (IgE) binding to MGL_1304, the component of QR. However, there has been no information on the immunological changes of type-I hypersensitivity to the sweat antigen in patients with well-controlled AD using topical corticosteroids (TCSs) and/or biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A recent study found that basophils are highly reactive to sweat antigens. In AD patients, type I hypersensitivity to sweat can be manifested by the release of histamine by patient basophil in response to semi-purified sweat antigen (QR) and the binding of IgE to MGL-1304 (a component of QR), suggesting that sweat may aggravate AD [60]. Basophils play a role in the mechanism of AD pruritus and are required for acute pruritus episodes in AD-related inflammation.…”
Section: Basophils and Admentioning
confidence: 99%
“…A recent study found that basophils are highly reactive to sweat antigens. In AD patients, type I hypersensitivity to sweat can be manifested by the release of histamine by patient basophil in response to semi-purified sweat antigen (QR) and the binding of IgE to MGL-1304 (a component of QR), suggesting that sweat may aggravate AD [60]. Basophils play a role in the mechanism of AD pruritus and are required for acute pruritus episodes in AD-related inflammation.…”
Section: Basophils and Admentioning
confidence: 99%